Action of X-rays on contracture frog muscle acetylcholine and atropine acetylcholine antagonism (Revista Española de Fisiología, 1945)
The methods of radiobiological researches carried out in order to study the effects of ionizing rays upon cellular permeability are criticized.The results previously obtained by the author in superior cervical ganglion by means of small amounts of roentgen rays are mentioned.Frog’s muscle (Rectus abdominis) irradiated with small dosis of roentgen-rays shows an increased isotonic response to acetylcholine which is ascribed to increased ≪reactivity≪ of the biological substratum according to the physico-chemical theories of Pharmacology.In order to support the considered hypothesis on roentgen rays action its effect on the acetylcholine-atropin antagonism is investigated and it is demonstrated that irradiated muscle recovers from the inhibitory action of atropine much earlier and more widely than non-irradiated muscle.